Development of an automated biaxial solar photovoltaic tracking system / Ahmad Maliki Omar ... [et al.] - Omar, Ahmad Maliki; Yahir, Muhamad Rizuan; Shaari, Sulaiman; Omar, Abdul Rahman (Institute of Research, Development and Commercialisation (IRDC), 2006)
This paper presents and describes a prototype product code-named SolT2A which is a system that tracks the position of the sun automatically across the celestial vault in two axes. This kind of system is typically used in a solar photovoltaic (PV) system in terrestrial applications to provide electrical power. It is designed and fabricated due to Malaysia's location near the equator, thus the solar altitude crosses the zenith and the azimuth reverses direction during the year. Thus the use of a static PV system is not maximised during half of the year. This situation can be addressed by using a two-axes solar tracking system. So far, Malaysia has not implemented such powertracking systems. Thus SolT2A has been designed and fabricated to address the problem by using a combination of electro-mechanical devices with an element of programming ingenuity and intelligence. Basically SolT2A measures solar irradiance at four points and makes comparisons in terms of the intensity received. These data are then analysed and processed by a controller before being sent to a DC motor that ensures the maximum amount of solar irradiance received on the PV panels all the time. Thus SolT2A is a system that maximises the power output of the PV panels to obtain the highest power output continuously. Based on field data, the maximum output open circuit voltage produced by the SolT2A tracking system and that with a static PV system is as much as 82 %. The overall increase in open circuit voltage production is between 15 to 20 % daily. With the technical know-how and proven prototype, Malaysia can look into joining the small and limited but niche pool of expertise in this area. This will not only give immediate socioeconomic impact to the population, but will give an upgrade to Malaysia as a country with expertise in the area. This concept could also be applied to defence systems. With further testing and improvement, SolT2A system can be further upgraded to reach a commercial stage. This will definitely be of commercial interest to the country.